Acetic Acid Treatment Enhances Drought Avoidance in Cassava (Manihot esculenta Crantz) - Utsumi, Yoshinori; Utsumi, Chikako; Tanaka, Maho; Ha, Chien Van; Takahashi, Satoshi; Matsui, Akihiro; Matsunaga, Tomoko M.; Matsunaga, Sachihiro; Kanno, Yuri; Seo, Mitsunori; Okamoto, Yoshie; Moriya, Erika; et al. (Frontiers in Plant Science, 2019)
External application of acetic acid has been recently reported to enhance the survival to drought in plants such as Arabidopsis, rapeseed, maize, rice and wheat, but the effects of acetic acid application on increased drought tolerance in woody plants such as a tropical crop “cassava” remain elusive. A molecular understanding of acetic acid-induced drought avoidance in cassava will contribute to the development of technology that can be used to enhance drought tolerance without resorting to transgenic technology or advancements in cassava cultivation. In the present study, morphological, physiological and molecular responses to drought were analyzed in cassava after the treatment with acetic acid. Results indicated that the acetic acid-treated cassava plants had a higher level of drought avoidance than water-treated, control plants. Specifically, higher leaf relative water content, and chlorophyll and carotenoid levels were observed as soils dried out during the drought treatment. Leaf temperatures in acetic acid-treated cassava plants were higher relative to leaves on plants pretreated with water and the increase of ABA content was observed in leaves of acetic acid-treated plants, suggesting that stomatal conductance and the transpiration rate in leaves of acetic acid-treated plants decreased to maintain relative water contents and avoid drought. Transcriptome analysis revealed that the acetic acid treatment increased the expression of ABA signaling-related genes, such as OPEN STOMATA 1 (OST1) and protein phosphatase 2C; as well as drought response and tolerance-related genes, such as outer membrane tryptophan-rich sensory protein (TSPO), and heat shock proteins. Collectively, the external application of acetic acid enhances drought avoidance in cassava through the upregulation of ABA signaling pathway genes and several stress response- and tolerance-related genes. These data support the idea that adjustments of the acetic acid application to plants is useful to enhance drought tolerance in order to minimize the growth inhibition in the agricultural field.